Lessons Learned from COVID-19 to better address future threats to global health security: A Critical Analysis of Experts Perspectives - Dicky Budiman; Neneng Nurlaela; Vivi Setiawaty; Cordia Chu (University of New South Wales, 2023)
Emerging infectious diseases have had a significant impact on the Asia-Pacific region in recent years, including a severe acute respiratory syndrome outbreak that occurred in 2002-2003, which had a substantial impact on several Asia-Pacific economies, the outbreak of highly pathogenic Asian avian influenza A (H5N1) that followed in 2006, strains of H1N1, and Middle East respiratory syndrome (MERS). There is an increasing frequency and impact of emerging infectious diseases (EID), as demonstrated by the current global outbreak of COVID-19 (coronavirus disease 2019). The Asia-Pacific region is particularly vulnerable to the spread of EID across national borders. In collaboration with the Ministry of Health of the Republic of Indonesia, the Asia Pacific Economic Cooperation (APEC) Health Working Group conducted an International Workshop on Managing Emerging Infectious Diseases (MEID) in Jakarta, Indonesia, on 12-16 September 2022. The workshop focused on a lesson-learning approach and aimed to strengthen global and domestic preparedness for the next pandemic.  Four key lessons can be drawn from the APEC region's COVID-19 pandemic. First, zoonotic outbreaks threaten health security, making One Health an urgent necessity. Secondly, collaboration and partnership are essential to combating the pandemic. Thirdly, decisive leadership is essential at all global and local levels. Finally, risk communication builds trust and acknowledges uncertainty during a crisis. These lessons could strengthen the evidence base for regional policy responses and better responses to future threats.